Phyllosphere bacterial assembly in citrus crop under conventional and ecological management - Carolinne R. Carvalho; Armando CF Dias; Sérgio K. Homma; Elke JBN Cardoso (PeerJ, 2020)
Divergences between agricultural management can result in different types of biological interactions between plants and microorganisms, which may affect food quality and productivity. Conventional practices are well-established in the agroindustry as very efficient and lucrative; however, the increasing demand for sustainable alternatives has turned attention towards agroecological approaches. Here we intend to explore microbial dynamics according to the agricultural management used, based on the composition and structure of these bacterial communities on the most environmentally exposed habitat, the phyllosphere. Leaf samples were collected from a Citrus crop (cultivated Orange) in Mogi-Guaçu (SP, Brazil), where either conventional or ecological management systems were properly applied in two different areas. NGS sequencing analysis and quantitative PCR allowed us to comprehend the phyllosphere behavior and µ-XRF (micro X-ray fluorescence) could provide an insight on agrochemical persistence on foliar tissues. Our results demonstrate that there is considerable variation in the phyllosphere community due to the management practices used in the citrus orchard, and it was possible to quantify most of this variation. Equally, high copper concentrations may have influenced bacterial abundance, having a relevant impact on the differences observed. Moreover, we highlight the intricate relationship microorganisms have with crop production, and presumably with crop yield as well.